Emilijos Adiklienės kraštotyrinė veikla ir archeologinis rinkinys Palangos kurorto muziejuje - Ziabreva, Viktorija (Archaeologia Lituana, 2017)
The etnographic activity of Emilija Adikliene and the archaeological collection of the Palanga Resort MuseumDuring the 1960s and 1970s, an active collection of antiquities took place in Palanga, thanks to an educator, Lithuanian scholar and ethnographer Emilija Adikliene. After her retirement in 1966, Adikliene became the chairwoman of the Monuments Protection and Ethnographic Society’s Palanga Division of the former Lithuanian Soviet Republic. Palanga community was encouraged to contribute to the newly emerging museum by donating any old items related to ethnography and cultural heritage. Ethnographers themselves actively participated in the ethnographic tours around Palanga. The archaeological collection of Adikliene, kept at the Palanga Resort Museum, mostly consists of archaeological items, first time published in this article and its appendix. The set mainly consists of archeological metal artifacts, a part of Kuršiai, Lamata tribes’ culture.
Keywords: Emilija Adikliene; Palanga; etnographers; archaeological collection; Curonians; Lamata